PEMBERDAYAAN BIMBINGAN BELAJAR MELALUI SOSIALISASI MEDIA BELAJAR SMART SPINNER - Adelia Putri (Jurnal Pengabdian Kepada Masyarakat Bersinergi Inovatif, 2023)
The purpose and activity is as a means to introduce a learning media for English subjects at the Master English tutoring place. The activity is in the nature of socialization and mentoring. The participants in the activity consisted of 5 people with details of student heads and two mentors from tutoring. The results of these activities are in the form of understanding students and mentors can operationalize learning media in the form of smart spinners for teaching and learning activities in English subjects. The survey results show that the media provided is quite good, effective, and interesting to use in teaching and learning English in class.